2007
DOI: 10.1243/09544062jmes336
|View full text |Cite
|
Sign up to set email alerts
|

A combustion model sensitivity study for CH4/H2 bluff-body stabilized flame

Abstract: Citation: HOSSAIN, M. and MALALASEKERA, W., 2007 Abstract: The objective of the current work is to assess the performance of different combustion models in predicting turbulent non-premixed combustion in conjunction with the k−ε turbulence model. The laminar flamelet, equilibrium chemistry, constrained equilibrium chemistry, and flame sheet models are applied to simulate combustion in a CH 4 /H 2 bluff-body flame experimentally studied by the University of Sydney. The computational results are compared to expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…Fine-tuning of the standard k-ε model constants can also be found in [6][7][8] in conjunction with EDC combustion model, where acceptable accuracy is reported. When used with laminar flamelet model, both the fine-tuned k-ε model and the RSM yielded acceptable results as reported in [10] and [11] respectively. Yilmaz et al [9] compared the fine-tuned k-ε model with large eddy simulation (LES) with two subgrid models; the Smagorinsky-Lilly and RNG/k-ε models.…”
Section: Turbulence Modelingmentioning
confidence: 73%
See 2 more Smart Citations
“…Fine-tuning of the standard k-ε model constants can also be found in [6][7][8] in conjunction with EDC combustion model, where acceptable accuracy is reported. When used with laminar flamelet model, both the fine-tuned k-ε model and the RSM yielded acceptable results as reported in [10] and [11] respectively. Yilmaz et al [9] compared the fine-tuned k-ε model with large eddy simulation (LES) with two subgrid models; the Smagorinsky-Lilly and RNG/k-ε models.…”
Section: Turbulence Modelingmentioning
confidence: 73%
“…The steady laminar flamelet model is known to perform better in terms of prediction of minor species. Several researchers [9][10][11] have used such model to simulate similar flames of CH 4 /H 2 . Yilmaz et al [9] calculated the Probability Density Function (PDF) for temperature, mixture fraction and major and minor species mass fractions and compared the flamelet model with equilibrium model, showing that flamelet model yields better results within the reaction zone.…”
Section: Modeling Of Turbulent Hydrogen Enriched Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that, compared to the equilibrium model, better results within the reaction zone were gained by flamelet model. The simulation of a nonpremixed hydrogenenriched methane bluff-body flame with respect to laminar flamelet model, equilibrium chemistry, flame sheet model, and constrained equilibrium chemistry which was done by Hossain and Malalasekera [28] proves that just major species could be predictable by flame sheet model. Although acceptable results for H 2 O mass fraction and combustion temperature could be achieved by the flame sheet model, overprediction of CO 2 is one of the weak points of this model.…”
Section: Hydrogen-enriched Gaseous Fuel Combustion Modellingmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) has been widely used to predict equipment performance or to optimize the device structure in fluid machinery, combustion systems, and many industries . Turbulence and the combustion model have very important influences on numerical results.…”
Section: Introductionmentioning
confidence: 99%